O fenômeno El Niño 2015 e os projetos hidro elétricos da Bacia do Rio São Francisco: o caso da Barragem de Sobradinho/BA - SANTOS, Marcelo Oliveira dos (2016)
Statistical studies based on historical series of frequency external dry event occurrences indicated for the year 2015 the probability of occurrence of the most intense El Niño with causes and severe consequences affecting the watershed region of the São Francisco River with repercussions on the questions volumetric and hydro in sobradinho dam. The methodological procedure used in this work was proposed treatment of information and data for bibliographic research on websites of regulators of water and energy companies involved in the management and operation of multi-purpose water systems and hydroelectric power generation. Highlighting the effects and assessing the impacts and consequences in Sobradinho dam as a reduction of irrigation, transport performance, increased operating costs impacting the performance of the regional economy. It found a precipitous reduction in the volume of Sobradinho dam whose volume of stock started the year 2015 with 18.88% reducing to less than 1% critical level in December. This situation is characterized as severe water stress reducing regulated flow downstream involving the entire irrigation system and the production of agriculture. It noted that the year 2015 was the El Niño intense with 18 years return period resulting great loss so far unquantified because of public officials and society are not prepared with damages accounting processes indicators. This study allowed a reality knowledge that helps identify suggestions and procedures to mitigate the effects of climate and ecological phenomenon, the burden caused and socioeconomic and environmental impacts on the region.